answersLogoWhite

0

7z - 3 = 11 + 3z ie 7z -3z = 11 + 3 4z = 14 z = 3.5 Check: (7 x 3.5) - 3; 11 + (3 x 3.5) 24.5 - 3 = 11 + 10.5 21.5 = 21.5 QED

User Avatar

Wiki User

15y ago

Still curious? Ask our experts.

Chat with our AI personalities

ViviVivi
Your ride-or-die bestie who's seen you through every high and low.
Chat with Vivi
ProfessorProfessor
I will give you the most educated answer.
Chat with Professor
RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa

Add your answer:

Earn +20 pts
Q: 7z-3 equals 11 plus 3z
Write your answer...
Submit
Still have questions?
magnify glass
imp